Factors Associated Quality of Life Patients with Coronary Stent in Dr Sardjito Hospital Yogyakarta - Rofiyati Rofiyati; Akhmadi Akhmadi; Heny Suseani Pangastuti (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2020)
Coronary heart disease is the highest cause of death in the world and constitutes 31% of causes of death worldwide. Installation of stent causes mortality rate due to CHD to decline and has proven to improve quality of life and reduce the frequency of angina. On the other hand, patients with coronary heart disease with heart stents have various health risks related to complications and other health factors that will affect their quality of life. This study aims to determine the factors associated with the quality of life of patients with heart stents in the Cardiovascular Polyclinic of Dr. Sardjito General Hospital Yogyakarta. This study is a cross-sectional study involving 94 samples of coronary heart patients with heart stents having a checkup the Cardiovascular Polyclinic at Dr Sardjito General Hospital, Yogyakarta. Quality of life was measured using Seattle Angina Questionaire and depression was measured using the BDI II scale (beck depression inventory). Data were analyzed using multivariate analysis with linear regression. The age factor is a significant factor related to the quality of life of patients with heart stents with p = 0.001 (p <0.05) with R: -0,366. Age is a factor associated with the quality of life of patients with heart stents.